(untitled) (Huellas, 2015)
This purpose of this paper is to analyze the role of rural women in the organization and creation of collective participation spaces, not only as a way of earning a living that may improve the living conditions of small family farmers but also as a way of resisting the territorial expulsion and the loss of their socio – cultural identity. To achieve this purpose, the paper analyzes a case study: The Steppe Crafts Market, an example of Supportive and Social Economy, which is located in the Pilcaniyeu Department,provinceofRio Negro. The analysis is based on the life-storytelling technique, starting from a thorough interview of one rural craftswoman. The results allow for understanding the way in which women create a working space and a income source that tend to the social reproduction of the household unit, combining production and reproduction and, at the same time, increasing self – esteem, the re-appraisal of their own culture and ancestral knowledge, the motivation for training in the craftsmanship art, in issues related to social and family economy, and in communal participation, among others.